Web-Based Caricature Sales Information System Using the FAST Method - Siregar, Nabilah Dewani Adha; Elsera, Marina; Hadinata, Edrian (Yayasan Cita Cendikiawan Al Kharizmi, 2022)
The use of information technology has become widespread throughout all sectors of society, including government, business, healthcare, and education. Dalis Art Medan is a digital art-focused online store that opened its doors in 2017. Dalis Art's current sales system still relies on Facebook and Instagram because it does not yet have e-commerce, which results in low sales. Reporting mistakes are common since Dalis Art sales transaction data is still manually entered. E-commerce has been suggested as a solution to Dalis Art's issue with developing its sales operation. The FAST (Framework for the Application of Systems Thinking) methodology is used in this study. The FAST technique incorporates system users more actively in each stage of system development, is more adaptable, can be produced with other methods, and can be customized to the author's standard demands. The goal of this study is to make it easier for customers to learn about and purchase products from Dalis Art. Benefits might give consumers quick access to information on the items in Dalis Art. The study's findings demonstrate how fast and accurately a web-based sales information system, including details on products, ordering procedures, and payments, can be accessible via this method.